Removal of toxic malachite green dye from aqueous environment using reduced magnetic graphene oxide as an efficient and reusable adsorbent. Issue 15 (13th October 2021) - Gul, Kashif; Khan, Hamayun; Muhammad, Niaz; Ara, Behisht; Zia, Tanveer Ul Haq
ABSTRACT: In the present study, reduced magnetic graphene oxide (rmGO) was synthesized and explored as an adsorbent for the removal of MG from the aqueous environment in a batch system. The successful synthesis of rmGO was confirmed from XRD, FT-IR and EDX spectral analyses. SEM images of rmGO show the irregular-sheet like morphological structure with anchored magnetic nanoparticles with enhanced thermal stability and 4.25 as point of zero charge (PZC). During the adsorption study, the best experimental conditions for various operating parameters such as pH (6.5), contact time (120 min), adsorbent dose (30 mg), temperature (358 K), and MG concentration (20 µgmL –1 ) were achieved. The data follows the pseudo-second-order kinetic and Langmuir-Freundlich adsorption models with maximum adsorption capacity of 158.95 mgg −1 . Moreover, the adsorption process was spontaneous/nonspontaneous and endothermic (13837.8 kJmol −1 ) in nature with the increased randomness at the solid-solution boundary. The rmGO was used for five consecutive adsorption cycles, maintain good adsorption capacity (reaching 115.4 ± 1.98 mgg −1 at the 5 th cycle) and selectively in a binary mixture (selectivity coefficient values for congo red, methylene blue and sunset yellow as 10.27, 10.16, and 9.30 respectively) on the adsorption toward MG dye. The efficient, recyclable, chemical and thermally stable nature of the synthesized rmGO declare it as a promising candidates for the treatment of colored water and wastewater.